The Caucasus and Central Asian republics at the turn of the twenty-first century : a guide to the economies in transition - Jeffries, Ian (Routledge studies of societies in transition, 2003)
The author presents a clear, detailed and accessible breakdown of the developments in the Caucasus (Armenia, Azerbaijan and Georgia) and the Central Asian republics of Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan.